Families' Experiences of Life in the Year after a Child's Critical Illness: Navigating the Road to a “New Normal” - Atkins, Ellie K.; John, Mary; Colville, Gillian (Journal of Pediatric Intensive Care, 2020)
Semistructured interviews were conducted with patients and family members (n = 18) postdischarge to examine how they managed their recovery in the year following a child's intensive care unit admission. Data were analyzed using the grounded theory. Participants described an ongoing need to develop and adapt their narratives about admission and recovery. Other key themes were as follows: just getting through, recognizing they had changed, striving for normality, and finding positive aspects related to their experiences. It took longer than they expected for families to build a coherent narrative of events postdischarge and to adjust to the “new normal.” Implications for health professionals are discussed.
Keywords: outcomes; qualitative; postintensive care syndrome; pediatric intensive care unit